2003
DOI: 10.1139/y02-154
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin-like growth factor-1 by the renin–angiotensin system during regression of cardiac eccentric hypertrophy through angiotensin-converting enzyme inhibitor and AT1 antagonist

Abstract: Angiotensin II (Ang II) mediates its effects through its non-tyrosine-kinase G protein coupled Ang-II type 1 receptor (AT1). Growing evidence indicates that a functional insulin-like growth factor-1 (IGF-1) tyrosine kinase receptor is required for Ang-II-induced mitogenesis. Along with Ang II, we have previously shown that changes in IGF-1 receptor binding at myofibers are causative agents for cardiac eccentric hypertrophy. This study investigated the interaction of the renin-angiotensin system with the IGF-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…In addition, there is sufficient evidence showing that IGF-I mRNA and protein increase in parallel with the development of cardiac hypertrophy (9). Furthermore, in the volume-overload model we have shown that cardiac myofibers have an increased receptor affinity to IGF-I, which corroborated with the induction of eccentric hypertrophy (20).…”
supporting
confidence: 59%
“…In addition, there is sufficient evidence showing that IGF-I mRNA and protein increase in parallel with the development of cardiac hypertrophy (9). Furthermore, in the volume-overload model we have shown that cardiac myofibers have an increased receptor affinity to IGF-I, which corroborated with the induction of eccentric hypertrophy (20).…”
supporting
confidence: 59%
“…In cultured neonatal rat cardiac fibroblasts, ANG II was shown to increase IGF1R expression; also, the mitogenic effect of IGF-I was partly mediated by RAS activation and the ensuing upregulation of IGF1R expression, which was abolished by ACE inhibitors (moexiprilat or enalaprilat) and ARB (CV11974, the bioactive candesartan metabolite) (415). In a rat model of cardiac hypertrophy by aortocaval shunt, IGF-I binding to its receptor in the myofibers was elevated, and treatment with an ACE inhibitor (captopril) or an ARB (losartan) resulted in regression of cardiac hypertrophy accompanied by an attenuation or normalization of increased IGF-I affinity (162). In kidney transplant patients with posttransplant erythrocytosis, treatment with ACE inhibitors reduced both the hematocrit and serum IGF-I; hematocrit and circulating IGF-I levels were positively related, suggesting that IGF-I contributes to the ACE inhibitor-induced decrease of hematocrit in these patients (295).…”
Section: Ras and Igf Signalingmentioning
confidence: 99%
“…In the work reported here, we carried out a time-course investigation in vivo to define the overall gene expression profile associated with stretch activation of the endocrine heart following an increase in venous return to the heart obtained by aorto-caval shunt (14,15,35). We found that the level of expression of the regulator of G-protein signaling Ras dexamethasone-induced protein 1 (RASD1) was particularly affected by VO.…”
mentioning
confidence: 99%